2016
DOI: 10.14393/bj-v32n4a2016-32806
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity, antioxidant activity and nutritional content of long-life tomato

Abstract: ABSTRACT:The increasing tomato demand for the food market motivates improvements and the use of new biotechnologies in this fruit's production. The hybrid crop stands out for fruit production resistant to rot and postharvest wilt (long-life crops). Within this context, consumption of genetically modified food deserves attention regarding the safety and nutritional aspects due to the fact that inclusion and/or overexpression of genetic traits can cause harm to human health in the short or long term. In this sce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…These observations are in agreements with previous studies indicated that free radicals arising during radiation-exposure can lead to DNA damage. If overproduction of theses radicals occurs, oxidative damage could lead to radiation-induced cytotoxicity; and MNi expression (HALLIWELL, 2002).So, determination of micronucleated cells and chromosome aberrations frequencies has a valuable role in monitoring populations exposed to natural or synthetic mutagenic agents (SILVA et al, 2016). Khabour et al (2013) suggested that various vitamin E isoforms, including gamma tocotrienol, protect against cytogenetic damage in humans.…”
Section: Discussionmentioning
confidence: 99%
“…These observations are in agreements with previous studies indicated that free radicals arising during radiation-exposure can lead to DNA damage. If overproduction of theses radicals occurs, oxidative damage could lead to radiation-induced cytotoxicity; and MNi expression (HALLIWELL, 2002).So, determination of micronucleated cells and chromosome aberrations frequencies has a valuable role in monitoring populations exposed to natural or synthetic mutagenic agents (SILVA et al, 2016). Khabour et al (2013) suggested that various vitamin E isoforms, including gamma tocotrienol, protect against cytogenetic damage in humans.…”
Section: Discussionmentioning
confidence: 99%
“…High-performance liquid chromatography (HPLC) is the most widely used technique in food analysis for measuring vitamins, carbohydrates, additives (antioxidants, colorants, artificial sweeteners, etc. ), proteins, amino acids, mycotoxins, triglycerides (TGs) in fats and oils, lipids, chiral compounds, and pigments (carotenoids, anthocyanines) (Chang et al, 1995;Tarrago-Trani et al, 2012;Silva et al, 2016;Colak et al, 2022).…”
mentioning
confidence: 99%